Glycan-related genes in human gut microbiota exhibit differential distribution and diversity in carbohydrate degradation and glycan synthesis - Takihara, Hayato; Okuda, Shujiro (Frontiers in Molecular Biosciences, 2023)
Interactions between humans and the gut microbiome occur by supplying nutrients to gut epithelial cells via short-chain fatty acids obtained from dietary carbohydrates or mucins and activating immunity via mucins’ degradation. The degradation of carbohydrates derived from food is an important function for organisms to obtain energy. However, since humans possess only 17 genes encoding carbohydrate-degrading enzymes, the gut microbiome is responsible for degrading plant-derived polysaccharides. Using the method for extracting glycan-related genes from the metagenomes constructed thus far, we calculated the distribution and abundance of different glycan-related genes in the healthy human gut metagenome. Glycan-related genes showed an abundance of 0.64–11.00, indicating large individual differences. However, the distribution of the classes of glycan-related genes was similar between the samples. In addition, the function of carbohydrate degradation was divided into three clusters, showing high diversity; however, the synthesis function was not divided, indicating low diversity. The substrates of enzymes for carbohydrate degradation between clusters were either plant-derived polysaccharides or biased toward degrading polysaccharides derived from other sources. These functional biases differ depending on the type of microorganism used. Based on these findings, we predicted that 1) diversity will be constant because the influence on the host by the transferase of gut bacteria is a function derived from the genome, and 2) diversity will be high because the influence on the host by the hydrolase of gut bacteria is affected by incoming dietary carbohydrates.